LAJU OKSIDASI LEMAK DAN MUTU ORGANOLEPTIK IKAN TERI NASI KERING (Stolephorus spp) SELAMA PENYIMPANAN DINGIN - A. Suhaeli Fahmi; Widodo Farid Ma'ruf; Titi Surti (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2014)
Polyunsaturated  fatty  acids  are  valuable  nutritional  content  to  be  kept  in  fish. Polyunsaturated  fatty  acids  are  easily  oxidized,  so  it  can  be  easily  rancid.  Moreover  lipid oxidation can cause damage to other food components because lipid oxidation produces reactive, toxic  and  carcinogenic  compounds.  This  paper  attempts  to  analyze  the  effect  of  dryingto  the oxidation rate of dried anchovy. This research used Peroxide Value (PV) to measure the oxidation rate. The results showed thatduring chilled storage, PV had irregular pattern, because peroxide is a reactive and derivable compound. Sensory test showed that at the end of storage (28 days), the dried anchovy was still accepted by panels.  Keywords :dried anchovy, lipid oxidation, chilled storage,peroxide value